Globular glial tauopathy, a newly recognized white matter tauopathy, with depression/anxiety disorder: report and review of classification - Kurdi, Maher; Saeed Alghamdi, Badrah; Parfitt, Jeremy; Cyn Ang, Lee (Folia Neuropathologica, 2021)
Several studies have recently described 4-repeat tauopathies that are characterized by the presence of globular glial inclusions. These inclusions are astrocytic or oligodendroglial, show extensive white matter involvement, and have a wide range of neuropathological and clinical presentations. Globular glial tauopathy (GGT) is classified into three subtypes according to clinical manifestations. Type I is characterized by frontotemporal lobar degeneration and represents a group of diseases with diverse clinical and histopathological features. Some of these disorders are associated with abnormal microtubule-associated protein tau gene. Type II presents as motor impairment due to pyramidal involvement, whereas type III is a combination of the features of types I and II. This report describes a rare case of GGT that manifested as depression and anxiety and demonstrates its neuropathological features. We have also compared the features of this case with those of previously reported cases and have revisited the classification.